Anaerobic digestion industries progress throughout the world. Issue 1 (April 2020) - Akhiar, Afifi; Ahmad Zamri, Mohd Faiz Muaz; Torrijos, Michel; Shamsuddin, Abd Halim; Battimelli, Audrey; Roslan, E; Mohd Marzuki, Mohamad Hanif; Carrere, Helene
Abstract: Anaerobic digestion is a process where microorganisms degrade organic matter in the absence of oxygen to produce biogas, mainly composed of methane and carbon dioxide. Recent years have seen a strong development of anaerobic digestion units worldwide, especially in USA, Europe and China. Countries like China, Germany, USA, Italy, UK and France are seen leading in the biogas sector in the world due to long establishment, intensive research and government incentives for renewable energy as well as waste management solution option. Asian countries have also shown their interests in the biogas technology. With more proper research and studies on-going, Asia will see the growth of biogas sector in the next few coming years. Even though African countries are in their primary phase to develop this biogas technology and there are still more hurdles to overcome, there have been interests, development and implementation work to apply this technology for its potential renewable energy production as well as its waste management solution.